Diagnosis of Carrion's disease by direct blood PCR in thin blood smear negative samples. - Juana del Valle Mendoza (Public Library of Science (PLoS), 2014)
Bartonella bacilliformis is the etiologic agent of Carrion's disease. This disease has two well established phases, the most relevant being the so called Oroya Fever, in which B. bacilliformis infect the erythrocytes resulting in severe anemia and transient immunosuppression, with a high lethality in the absence of adequate antibiotic treatment. The presence of B. bacilliformis was studied in 113 blood samples suspected of Carrion's disease based on clinical criteria, despite the absence of a positive thin blood smear, by two different PCR techniques (using Bartonella-specific and universal 16S rRNA gene primers), and by bacterial culture. The specific 16S rRNA gene primers revealed the presence of 21 B. bacilliformis and 1 Bartonella elizabethae, while universal primers showed both the presence of 3 coinfections in which a concomitant pathogen was detected plus Bartonella, in addition to the presence of infections by other microorganisms such as Agrobacterium or Bacillus firmus. These data support the need to implement molecular tools to diagnose Carrion's disease.